1994
DOI: 10.1007/bf00335177
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial hemorrhage due to rupture of an arteriovenous malformation in a full-term neonate

Abstract: A case of neonatal intracerebral hemorrhage (ICH) secondary to rupture of an arteriovenous malformation (AVM) is reported. The baby began to vomit frequently 9 h after birth. Computed tomographic scan revealed the presence of an ICH. Intravenous digital subtraction angiography (IVDSA) demonstrated an AVM, which was successfully excised on the 2nd day after birth. It is stressed that IVDSA is safe and noninvasive in comparison with conventional angiography and is useful for diagnosis of cerebral vascular diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In 8 cases (12%) the diagnosis was not reached until autopsy [15,19,76,80]. Nineteen infants (29%) had ICH due to AVM rupture [5,13,17,30,32,41,56,64,71,72,84,87,93,96]. The bleed from the AVM was (in declining order of frequency), intraventricular [5,13,27,32,41,72], intracerebral [30,41,87,89,93] and/or subdural [5, 56,71,89].…”
Section: Arteriovenous Malformations In Infantsmentioning
confidence: 97%
See 1 more Smart Citation
“…In 8 cases (12%) the diagnosis was not reached until autopsy [15,19,76,80]. Nineteen infants (29%) had ICH due to AVM rupture [5,13,17,30,32,41,56,64,71,72,84,87,93,96]. The bleed from the AVM was (in declining order of frequency), intraventricular [5,13,27,32,41,72], intracerebral [30,41,87,89,93] and/or subdural [5, 56,71,89].…”
Section: Arteriovenous Malformations In Infantsmentioning
confidence: 97%
“…(H&E) failure, transient neurological deficits, permanent neurological compromise and even death. It has been suggested that digital subtraction angiography with the intravenous contrast injected through the umbilical vein [28,45] or a peripheral vein [30] has fewer complications than intraarterial angiography, but then the image resolution is far from optimal. On the other hand, magnetic resonance angiography (MRA) technology has evolved at a tremendous pace in recent years.…”
Section: Diagnosing the Ich In An Infantmentioning
confidence: 99%